1999
DOI: 10.1016/s0370-2693(99)00438-4
|View full text |Cite
|
Sign up to set email alerts
|

A redetermination of the neutrino mass-squared difference in tri-maximal mixing with terrestrial matter effects

Abstract: We re-fit for the neutrino mass-squared difference ∆m 2 in the threefold maximal (ie. tri-maximal) mixing scenario using recent CHOOZ and SUPER-K data, taking account of matter effects in the Earth. While matter effects have little influence on reactor experiments and proposed long-baseline accelerator experiments with L < ∼ 1000 km, they are highly significant for atmospheric experiments, suppressing naturally ν e mixing and enhancing ν µ − ν τ mixing, so as to effectively remove the experimental distinction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 36 publications
7
153
0
Order By: Relevance
“…As indicated in Section 1, intermediate baseline reactor experiments, such as CHOOZ [15] and PALO-VERDE [16], in fact provide the best limits on ν e (actuallyν e ) mixing at the atmospheric scale (in terms of the vacuum mixing matrix, the interpretation of the atmospheric experiments themselves can be seriously obscured by terrestrial matter effects, which tend to suppress ν e -mixing and enhance ν τ -mixing [19] in the high-energy limit). Reactor experiments, utilising very low energy (anti) neutrinos and with existing baselines much shorter than the matter-oscillation length in the Earth, turn out to be almost completely immune to matter effects [20].…”
Section: The Trend Of the Datamentioning
confidence: 99%
“…As indicated in Section 1, intermediate baseline reactor experiments, such as CHOOZ [15] and PALO-VERDE [16], in fact provide the best limits on ν e (actuallyν e ) mixing at the atmospheric scale (in terms of the vacuum mixing matrix, the interpretation of the atmospheric experiments themselves can be seriously obscured by terrestrial matter effects, which tend to suppress ν e -mixing and enhance ν τ -mixing [19] in the high-energy limit). Reactor experiments, utilising very low energy (anti) neutrinos and with existing baselines much shorter than the matter-oscillation length in the Earth, turn out to be almost completely immune to matter effects [20].…”
Section: The Trend Of the Datamentioning
confidence: 99%
“…2). In addition, we revealed that the conventional tri-bimaximal mixing (TBM) ansatz [45] is realized as a special case of the Z s 2 group with k = 2 , under which Z s 2 ⊗ Z µ−τ…”
Section: Solar Mixing Angle Not Affected By Soft Breakingmentioning
confidence: 99%
“…For instance, to predict the conventional tri-bimaximal mixing [45] only needs to assign |k| = 2 in our construction, leading to tan θ s = 1 √ 2…”
mentioning
confidence: 99%
“…Harrison, D.H. Perkins and W.G. Scott [20] before the SNO and KamLAND data came out, and had been studied by them and by Z.-Z. Xing [21,22].…”
Section: Note Addedmentioning
confidence: 99%